The BALB/c Mouse Model for the Evaluation of Therapies to Treat Infections with Aerosolized Burkholderia pseudomallei - Michelle Nelson; Kay B. Barnes; Carwyn H. Davies; Christopher K. Cote; J. Matthew Meinig; Sergei S. Biryukov; David N. Dyer; Ondraya Frick; Henry Heine; Denise A. Pfefferle; Amanda Horstman-Smith; Julie Barbaras; et al. (MDPI AG, 2023)
Burkholderia pseudomallei, the causative agent of the disease melioidosis, has been isolated from the environment in 45 countries. The treatment of melioidosis is complex, requiring lengthy antibiotic regimens, which can result in the relapse of the disease following treatment cessation. It is important that novel therapies to treat infections with B. pseudomallei be assessed in appropriate animal models, and discussions regarding the different protocols used between laboratories are critical. A 'deep dive' was held in October 2020 focusing on the use of the BALB/c mouse model and the inhalational route of infection to evaluate new antibiotic therapies.